Targeted metabolomics of sulfated bile acids in urine for the diagnosis and grading of intrahepatic cholestasis of pregnancy - Yuchao Li; Xiaoqing Zhang; Jianbo Chen; Chengya Feng; Yifan He; Yong Shao; Min Ding (Genes and Diseases, 2018)
Intrahepatic cholestasis of pregnancy (ICP) is related to cholestatic disorder in pregnancy. Total urinary sulfated bile acids (SBAs) were found increased in ICP. We distinguished the metabolic profiling of urinary SBAs in ICP to find potential biomarkers for the diagnosis and grading of ICP. The targeted metabolomics based on high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was used to analyze urinary SBAs profiling in mild and severe ICP cases, as well as healthy controls. 16 kinds of urinary SBAs were determined by HPLC-MS/MS. Sulfated dihydroxy glycine bile acid (di-GBA-S), glycine cholic acid 3-sulfate (GCA-3S), sulfated dihydroxy taurine bile acid (di-TBA-S) and taurine cholic acid 3-sulfate (TCA-3S) increased significantly in ICP group compared with the control group. Seven kinds of SBAs were significantly different (p < 0.05) between the ICP group and the control group, with the variable importance in the projection (VIP) value more than one by the orthogonal partial least squares discriminant analysis (OPLS-DA). GCA-3S was well-suited to be used as the biomarker for the diagnosis of ICP with the sensitivity of 100% and specificity of 95.5%. A multi-variable logistic regression containing GCA-3S and di-GBA-S-1 was constructed to distinguish severe ICP from mild ICP, with the sensitivity of 94.4% and specificity of 100%. The developed HPLC-MS/MS method is suitable for the measurement of urinary SBAs profiling. Moreover, the urinary SBAs in the metabolomic profiling have the potential to be used as non-intrusive biomarkers for the diagnosis and grading of ICP. Keywords: Biomarker, HPLC-MS/MS, Intrahepatic cholestasis of pregnancy, Sulfated bile acids, Targeted metabolomics, Urine